How methanotrophs respond to pH: A review of ecophysiology - Yao, Xiangwu; Wang, Jiaqi; Hu, Baolan (Frontiers in Microbiology, 2023)
Varying pH globally affects terrestrial microbial communities and biochemical cycles. Methanotrophs effectively mitigate methane fluxes in terrestrial habitats. Many methanotrophs grow optimal at neutral pH. However, recent discoveries of methanotrophs in strongly acidic and alkaline environments. Here, we summarize the existing knowledge on the ecophysiology of methanotrophs under different pH conditions. The distribution pattern of diverse subgroups is described with respect to their relationship with pH. In addition, their respond to pH stress, consisting of structure-function traits and substrate affinity traits are reviewed. Furthermore, we propose a putative energy trade-off model aiming at shedding light on the adaptation mechanisms of methanotrophs from a novel perspective. Finally, we take an outlook on methanotrophs’ ecophysiology affected by pH, which would offer new insights into methane cycle and global climate change.